Drought but not population density influences dietary niche breadth in white‐tailed deer in a semiarid environment. Issue 12 (23rd December 2014) - Folks, Donald J.; Gann, Kory; Fulbright, Timothy E.; Hewitt, David G.; DeYoung, Charles A.; Wester, David B.; Echols, Kim N.; Draeger, Don A.
Abstract : A premise in ungulate foraging theory is that animals become less selective and expand the breadth of their dietary niche as the availability of palatable forage declines with increasing herbivore population density or drought. Increased niche variation resulting from intraspecific competition is thought to create less similar diet composition and decreased diet overlap between individuals within a population at higher densities than between individuals within less dense populations. These ideas were largely developed in relatively mesic environments and their applicability to ungulate foraging in semiarid environments is unclear. We tested the idea that white‐tailed deer ( Odocoileus virginianus ) contract dietary niche breadth; reduce dietary plant species diversity, richness, and evenness; and become more individualistic in forage choices in response to a fourfold difference in population density (12 deer/km 2 versus 50 deer/km 2 ) in semiarid shrubland in Texas, USA. We used the bite count method to determine diet composition of tame female white‐tailed deer seasonally during summer 2009 to spring 2011. We were able to determine impacts of drought on foraging dynamics a posteriori because sampling during each season fortuitously occurred under both drought and non‐drought conditions. Population density did not affect diet richness, diversity, breadth, evenness, overlap, and similarity. Diet richness, diversity, breadth, and evenness tended to be greater in non‐drought conditions. For white‐tailed deer, the idea that dietary niches expand in response to increasing population density is not robust across environments. In semiarid environments, variation in precipitation has a much stronger influence on dietary niche breath and intraspecific diet overlap of deer than population density does.